Analysis of Two-Phase Cavitating Flow with Two-Fluid Model Using Integrated Boltzmann Equations (Advances in Applied Mathematics and Mechanics, 2013)
In the present work, both computational and experimental methods are employedto study the two-phase flow occurring in a model pump sump. The two-fluidmodel of the two-phase flow has been applied to the simulation of the three-dimensionalcavitating flow. The governing equations of the two-phase cavitating floware derived from the kinetic theory based on the Boltzmann equation. The isotropicRNG $k-ε-k_{ca}$ turbulence model of two-phase flows in the form of cavity number insteadof the form of cavity phase volume fraction is developed. The RNG $k-ε-k_{ca}$ turbulencemodel, that is the RNG $k-ε$ turbulence model for the liquid phase combinedwith the $k_{ca}$ model for the cavity phase, is employed to close the governing turbulentequations of the two-phase flow. The computation of the cavitating flow through amodel pump sump has been carried out with this model in three-dimensional spaces.The calculated results have been compared with the data of the PIV experiment. Goodqualitative agreement has been achieved which exhibits the reliability of the numericalsimulation model.